1995
DOI: 10.1007/bf01273897
|View full text |Cite
|
Sign up to set email alerts
|

Subject-matter knowledge and knowledge about students as sources of teacher presentations of the subject-matter

Abstract: Pedagogical content knowledge is made up of several components. In this paper we concentrate on one of these: teachers' planned presentations of the subject-matter. We deal with two main sources of this component of pedagogical content knowledge: knowledge about the subject-matter and knowledge about students. Illustrations are given in two mathematical domains: functions and undefined mathematical operations. The paper concludes with a discussion of the nature of teachers' knowledge and the interconnections b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
18

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(93 citation statements)
references
References 10 publications
1
68
0
18
Order By: Relevance
“…There are only a few large-scale studies via paper-and-pencil tests available (Even & Tirosh, 1995;Schmelzing et al, 2013;Rowan et al, 2001), especially in the field of physics (Etkina, 2010). To gain an insight into the methodology of paperand-pencil questionnaire, related studies were classified into two groups and specifically reviewed as follows.…”
Section: Large-scale Studies Based On Paper-and-pencil Instruments Fomentioning
confidence: 99%
“…There are only a few large-scale studies via paper-and-pencil tests available (Even & Tirosh, 1995;Schmelzing et al, 2013;Rowan et al, 2001), especially in the field of physics (Etkina, 2010). To gain an insight into the methodology of paperand-pencil questionnaire, related studies were classified into two groups and specifically reviewed as follows.…”
Section: Large-scale Studies Based On Paper-and-pencil Instruments Fomentioning
confidence: 99%
“…As for the components of the knowledge of the students and their teaching practices, S2 has a shift from the PCK to implentation PCK in teaching practice by category down. Even and Tirosh (1995) investigated the teacher's knowledge of the students and found that teachers are reluctant to try to understand the source of the students' responses although they need this information to make appropriate instructional decisions to help students learn. When students give a wrong answer they tend to explain the correct answers rather than asking students how they find the answer.…”
Section: Pck Subject 2 (S2)mentioning
confidence: 99%
“…Aynı şekilde öğretmenlerin öğrenci çözümlerini değerlendirmelerindeki eksikliklerde yine alan bilgisinin eksikliğinin bir sonucu olarak değerlendirilmiştir (Even & Tirosh, 1995).…”
unclassified
“…Bu konudaki sınırlı çalışmalar içinde bu nedenler Baştürk'ün (2009) öğretmen adayları ile yaptığı çalışmada bildirilen nedenler ile benzerlik göstermektedir. Öğretmenlerin etkili müdahaleyi yapabilmek için öğrencinin kavram yanılgısının altında yatan nedeni tahmin edebilmesi ve öğrenci algısının altında yatan muhakemeyi anlayabilmeleri gereğinden bahsedilmektedir (Even & Tirosh, 1995). Ancak mesleki deneyim yılına bağlı olmaksızın araştırmaya katılan öğretmenlerin hiç biri öğrencinin yapabilmiş olduğu muhakemeden bahsetmemiştir.…”
unclassified